Dietary phosphorus restriction induced phospholipid deficiency, endoplasmic reticulum stress, inflammatory response and gut microbiota disorders in Lateolabrax maculatus - Wu, Zixiang; Guo, Jiarong; Lu, Kangle; Song, Kai; Wang, Ling; Ma, Ruijuan; Zhang, Chunxiao; Li, Xueshan (Frontiers in Immunology, 2025)
This study evaluated the effects of low phosphorus on spotted seabass (Lateolabrax maculatus) from the perspective of phospholipid content and function, endoplasmic reticulum (ER) stress, inflammatory response and gut microbiota. Two diets were prepared to contain available phosphorus levels of 0.37% (low-phosphorus, LP) and 0.75% (normal-phosphorus, NP) and feed fish (3.53 ± 0.34 g) to satiety twice daily for 10 weeks. Compared with fish fed the NP diet, fish fed the LP diet showed lower body weight gain and higher abdominal fat percentage. Further studies showed that the LP diet decreased the content of phospholipid in the serum, liver, and abdominal fat tissue and induced ER stress and disruption of lipid metabolism in both of the liver and abdominal fat tissue and inflammatory responses in abdominal fat tissue. Furthermore, compared with fish fed the NP diet, the LP diet reduced microbial diversity in the gut. In contrast to fish fed the NP diet, fish fed the LP diet exhibited a decrease in the abundance of potential metabolically promoted probiotics (e.g., Lactococcus lactis) and an increase in the abundance of potential pathogenic bacteria (e.g., Plesiomonas) in the gut. The results of PICRUSt2 functional prediction also validated the metabolic disorders occurring in fish fed the LP diet as well as the reduced metabolic capacity. These results suggested that the LP diet decreased phospholipid content, induced ER stress and inflammatory responses then disturbed lipid metabolism and gut microbiota in spotted seabass. These negative effects contributed to poorer growth and higher percentage of abdominal fat in spotted seabass fed the LP diet than those of spotted seabass fed the NP diet.